2891 Designing the GI Cloud - Shergill, Annie; Narasimhan, V. Lakshmi; Garg, Deepti; Sala, Amruth K. (The American journal of gastroenterology, 2019)
INTRODUCTION:Gastroenterology is a field of medicine that has its roots deeply embedded in the technological revolution of the 21st century. It emerges as a specialty dominated by ever-evolving imaging and diagnostic modalities that have surpassed archaic means of diagnosing and treating various GI disorders. This article highlights advancement in Cloud computing technology that has the potential to change the way healthcare professionals in GI work in the inpatient and outpatient setting. Cloud based technology for storing, retrieving and manipulating patient specific data is set to transcend from being used in government or corporate organizations to outpatient and inpatient GI services.METHODS:A comprehensive review of cloud computing and its application to facilitate a cohesive method of functioning that ties one end of the expanding patient database and procedural reporting to the other end of effective reproduction and recall of this data.RESULTS:An emerging challenge in the field of GI today is the need to accommodate an enlarging patient database, while concurrently balancing a myriad of quality determining factors, such as information security, privacy, reliability and interoperability of data. Considering this, Cloud based technology emerges as the single most vied advancement to address this issue. The Cloud environment refers to the practice of using a network of remote servers hosted on the internet to store, manage and process data, rather than a local server or a personal computer. Cloud computing can transform the way information technology is consumed and managed, resulting in improved cost efficiencies, accelerated innovation and the ability to scale applications on demand.CONCLUSION:Groundbreaking advancements always stem from the absolute need to bring about a change in the existing methodology. There is a void emerging from the disparity between increasing volume of patient specific data and a concomitant lack of infrastructure to handle the same. There is also an increasing need to introduce automated features that facilitate patient specific data storage, search, retrieval and processing. Hence, the quest to pursue cloud based technology as the mainstay of data handling and processing in GI. In a dynamic field like GI, brand new concepts are crucial to challenge those that already exist and alternative techniques and modalities are vital. Therefore, Cloud computing offers an efficient solution to several data processing problems and issues encountered in GI.